UPAYA PENCEGAHAN VIRUS (COVID-19) MELALUI KETERLIBATAN PENGABDIAN KKM-16 UNIBA 2021 DALAM PENYEMPROTAN DISINFEKTAN DAN PENTINGNYA MENJAGA PROKES DI DESA PANYAUNGAN JAYA, KECAMATAN CIOMAS KABUPATEN SERANG - Pramudi Harsono; Abdul Said Al Abad; Roby Muhammad Ihza; Yasinta Soo; Ethana Harits Bryano (Indonesian Collaboration Journal of Community Services, 2021)
Corona virus which is often called Covid-19 is a group of viruses that can cause respiratory infections caused by the SARS-CoV-02 virus from the large family of corona viruses. In many cases, this virus causes mild respiratory infections such as influenza alone, but the virus can cause severe respiratory infections, namely pneumonia plus congenital diseases which are often called comorbid. In the Serang district, of course, the spread of the COVID-19 virus is certainly not too large. In order to prevent and spread and break the chain of covid-19, namely through spraying disinfectants as one way to do it with the standard disinfection method using disinfectant liquid as a prevention effort and while maintaining health protocols (prokes), through 5 M (wearing Masks, Make Keeping distance, Make Washing hands, Restricting mobility and Make Staying away from crowds). So the efforts of the KKM-16 team at the University of Bina Bangsa Banten 2021 to prevent covid-19 by spraying disinfectants in Panyaungan Jaya Village, Ciomas sub-district, Serang. The method in carrying out this activity is to permit the Village Head first, then carry out prevention socialization and share tutorials for making disinfectants properly and correctly and spraying at various points in public places and maintaining health procedures. So it is hoped that it can break the chain of the spread of ovid-19 in Panyaungan Jaya Village, Ciomas sub-district, Serang